-8z+5=7z+5

Simple and best practice solution for -8z+5=7z+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8z+5=7z+5 equation:



-8z+5=7z+5
We move all terms to the left:
-8z+5-(7z+5)=0
We get rid of parentheses
-8z-7z-5+5=0
We add all the numbers together, and all the variables
-15z=0
z=0/-15
z=0

See similar equations:

| 3(p-7)=7-p | | -9v-6(7+6)=48 | | 60.v=15 | | 12=10.5x+1/2 | | 355-5x=177.5 | | 6z-2z=+4 | | k^2-12k+4=0 | | 5x+13+2x=27 | | 4/3=2/3(t+t/3) | | 10y+7=90 | | 12=5c-2 | | w+2.44=9.53 | | 8-7(4-3k)=-83 | | 5x+3(2x+8)=2(x+6) | | 30s+240=50s-160 | | 15.77+0.09x=16.27+0.12x | | k+k-6=2(k-3) | | 3y+9=+4y | | -7=n+3*4n | | 10y+7=180 | | 2x+12=x–3 | | 11x-1+12x+13=12 | | 6=18/t | | -8n-4n+17=23 | | 10x-77=7 | | -178/107=n | | 4y+9=+3y | | -36x=-18 | | -302/95=n | | 3x+-5=-26 | | 11(b+2)=8(b+5) | | 10(n+2)=4/5(5+15n) |

Equations solver categories